Perspectives on disability & rehabilitation contesting assumptions, challenging practice - Hammell, Karen Whalley (Philadelphia, Pa. Churchill Livingtone Elsevier, 2006)
It explores issues that are central to rehabilitation, such as the nature of the body, the idea of independence, the rehabilitation process, evidence-based practice and client-centred practice. Seeking always to ground theoretical ideas in the realities of every-day rehabilitation practice, and drawing from a wealth of research evidence, the book continually examines the implications of these perspectives for the education, practice, service delivery, research and theoretical development of the rehabilitation professions.
Provides an introduction to many of the theoretical perspectives on disability. This book aims to help readers challenge the taken-for-granted nature of traditional knowledge and assumptions within the rehabilitation, health and community care industries. It also encourages a more critical approach to the nature of rehabilitation.
Exploring the assumptions underpinning rehabilitation -- Normality and the classification of difference -- Disability and deviance from the norm -- Theoretical models of disability -- The cultural perpetuation of disability -- The body and physical impairment -- Disability, rehabilitation and liminality -- Rehabilitation fundamentals -- Client-centred philosophy: exploring privalege and power -- Researching disability and rehabilitation -- Contesting assumptions; challenging practice.
Keywords: People with disabilities -- Rehabilitation; Sociology of disability; Disabilities